1996
DOI: 10.1128/jvi.70.10.7004-7012.1996
|View full text |Cite
|
Sign up to set email alerts
|

JC virus infection of hematopoietic progenitor cells, primary B lymphocytes, and tonsillar stromal cells: implications for viral latency

Abstract: The human polyomavirus JC virus (JCV) infects myelin-producing cells in the central nervous system, resulting in the fatal demyelinating disease progressive multifocal leukoencephalopathy (PML). JCV-induced PML occurs most frequently in immunosuppressed individuals, with the highest incidence in human immunodeficiency type 1-infected patients, ranging between 4 and 6% of all AIDS cases. Although JCV targets a highly specialized cell in the central nervous system, infection is widespread, with more than 80% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(102 citation statements)
references
References 35 publications
2
99
0
1
Order By: Relevance
“…This may be a general feature of human polyomaviruses, as tonsillar tissues can harbor both JCV 21 and BKV 22 DNA and tonsillar stromal cells have been shown to be susceptible to JCV infection. 23 Blood cellderived MCPyV positivity of the tonsils could not be completely ruled out as only serum samples (all of which tested negative for MCPyV DNA) obtained at the time of operation were available from our tonsillectomy patients. The potential presence of MCPyV in blood cells of immunocompetent individuals as opposed to serum is an interesting topic for further research.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a general feature of human polyomaviruses, as tonsillar tissues can harbor both JCV 21 and BKV 22 DNA and tonsillar stromal cells have been shown to be susceptible to JCV infection. 23 Blood cellderived MCPyV positivity of the tonsils could not be completely ruled out as only serum samples (all of which tested negative for MCPyV DNA) obtained at the time of operation were available from our tonsillectomy patients. The potential presence of MCPyV in blood cells of immunocompetent individuals as opposed to serum is an interesting topic for further research.…”
Section: Discussionmentioning
confidence: 99%
“…The tonsils have been proposed to be a primary site of infection for the human polyomaviruses based upon the detection of BKV and JCV in this tissue and upon the ability of JCV to replicate in cultures of tonsillar stromal cells [Goudsmit et al, 1982;Monaco et al, 1996Monaco et al, , 1998]. The detection of the same rearranged form, BKV(TU), in leukocytes (this study) and in urine [Sundsfjord et al, 1990], strengthens the hypothesis that lymphocyte-mediated transport of rearranged BKV variants occurs from a primary site of infection (e.g., tonsils) to secondary sites (e.g., kidney) within the body.…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, JCV Mad-4 in vitro infectability was demonstrated in the following: primary CD34 ϩ cells derived from human fetal liver; the CD34 ϩ hematopoietic precursor cell lines KG-1 and KG-1a; tonsillar stromal cells derived from non-PML patients; and CD19 ϩ B lymphocytes derived from the tonsils and peripheral blood of non-PML patients [79]. When treated with phorbol esters, the KG-1 cells differentiated into cells resembling mature macrophages that, like promonocytic U937 cells, were not susceptible to JCV infection.…”
Section: Host Range Extended To Lymphocytesmentioning
confidence: 99%
“…Also, the infected lymphocyte cultures were able to transmit infection to HFGC cultures but showed only baseline HA titers for JCV as compared with the high titers observed from the infected tonsillar stromal cultures. Due to their permissiveness to infection and their high rates of virus production it has been suggested that tonsillar stromal cells, which have substantial lymphocytic interaction in vivo, could serve as the initial site of JCV infection by either respiratory or oral route [79]. A current list of human tissues with resident cell types that demonstrate in vivo JCV infection are summarized in Table 2.…”
Section: Host Range Extended To Lymphocytesmentioning
confidence: 99%